AB0899 Depression and anxiety correlate with disease-related characteristics and quality of life in chinese patients with gout: a cross-sectional study. (15th June 2017) - Fu, T; Cao, H; Yin, R; Zhang, L; Zhang, Q; Li, L; Feng, X; Gu, Z
Abstract : Background: Depression and anxiety are common worldwide and may lead to disease aggravation and decreased health-related quality of life (HRQoL). The increasing prevalence of depression and anxiety in gout patients is associated with demographic and gout characteristics. However, there are currently no known reported studies related to the association between HRQoL and depression/anxiety. Objectives: This cross-sectional study aims to evaluate the prevalence of depression and anxiety and investigate the potential risk factors for depression and anxiety in Chinese gout patients. Methods: A self-report survey was administered to 193 gout patients and 208 healthy individuals from September 2015 to September 2016. Patients were asked to complete a set of standardized self-report questionnaires [Visual Analog Scale (VAS), Health Assessment Questionnaire-Disability Index (HAQ-DI), Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder (GAD-7) questionnaire, Short Form 36 health survey (SF-36)]. Independent samples t-tests, χ 2 analyses, and logistic regression were used to analyze the data. Results: We found 15% of gout patients had depression, and 5.2% had anxiety, which were significantly higher than the healthy controls (1.4 and 1.0%, respectively). There were significant correlations among education, pain, disease duration, stage of gout, disability, number of tophi, presence of tender joints, HRQoL, and psychological status. Meanwhile, logistic regression analysis identified number of tophi, HAQ-DI, and MH scale as predictors of depression in gout patients. Education, GH, and VT domains were significantly accounted for anxiety. Conclusions: The prevalence of depressive and anxious symptoms among gout patients was higher than healthy individuals. Education, disability, tophi and HRQoL were important risk factors linked to this disorder in Chinese gout population. These findings suggested medical personnel should pay more attention to the psychological health of gout patients and make objective interventions to relieve their depression and anxiety, especially those with low education level, more than two tophi, severe disability, and poor HRQoL. Acknowledgements: This study was supported by Grants from the Chinese National Natural Science Foundation (no. 81671616 and 81471603). Disclosure of Interest: None declared